2017
DOI: 10.17221/344/2017-pse
|View full text |Cite
|
Sign up to set email alerts
|

Potassium impact on nitrogen use efficiency in potato - a case study from the Central-East Europe

Abstract: During the last century, potato (Solanum tuberosum L.) has become a worldwide elementary staple food. The key reason for this process is the high nutritional value of potato as a carbohydrate source, storability, and ease and divergent uses. Breeding programmes resulted in new cultivars with improved yield potential (Brown 2011). In spite of a significant biological progress during the recent decades, actual yields in many countries are unsatisfactory and fail to rise further. Between 2004 and 2013, the world … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…Cereal crops, including wheat, require adequate K nutrition to balance higher N fertilizer rates applied to optimize yields (Kansas State Agronomy, 2019). Guo et al (2019) showed that K supply has a significant influence on the regulation of wheat plant growth, photosynthesis, and nutrient uptake, and identified a positive interaction between N and K. Other authors have reported that the consequences of N metabolism (Hu et al, 2016), N uptake and NUE (Grzebisz et al, 2017), and C-N balance (Hu, Coomer, Loka, Oosterhuis, & Zhou, 2017) are improved by K fertilizer application. Furthermore, results by Guo et al (2019) indicated a positive synergistic interaction between N and K on nutrient uptake and yield production in wheat.…”
Section: Core Ideasmentioning
confidence: 95%
“…Cereal crops, including wheat, require adequate K nutrition to balance higher N fertilizer rates applied to optimize yields (Kansas State Agronomy, 2019). Guo et al (2019) showed that K supply has a significant influence on the regulation of wheat plant growth, photosynthesis, and nutrient uptake, and identified a positive interaction between N and K. Other authors have reported that the consequences of N metabolism (Hu et al, 2016), N uptake and NUE (Grzebisz et al, 2017), and C-N balance (Hu, Coomer, Loka, Oosterhuis, & Zhou, 2017) are improved by K fertilizer application. Furthermore, results by Guo et al (2019) indicated a positive synergistic interaction between N and K on nutrient uptake and yield production in wheat.…”
Section: Core Ideasmentioning
confidence: 95%
“…The (Chen et al, 2016;Luo et al, 2018). Studies showed that co-applied N with P or K could enhance yield production in plant by positive interaction between N and P, N, and K (De Groot et al, 2003;Grzebisz et al, 2017;Xu & Li, 2014).…”
Section: Yieldmentioning
confidence: 99%
“…Therefore, the present results were compared with those reported for potatoes, due to similar agronomic practices in both crop species (wide-row sowing) and yield specificity (main yield with high sugar content, below the soil surface). In a study by Stolarski et al [48], JA cultivated as a perennial plant for energy purposes produced from 10 to 19 kg of the DMY (aerial biomass) per kg of applied N. Grzebisz et al [55] reported that an increase in potato tuber yield ranged from 40 to 97 kg per kg of applied N depending on soil and climatic conditions (Poland, the Czech Republic, Albania), N rates, and cultivar. The agronomic efficiency of N fertilization was lowest in the growing season characterized by considerable precipitation deficiency.…”
Section: Effect Of N Fertilization On Agronomic N-indicesmentioning
confidence: 99%
“…The agronomic efficiency of N fertilization was lowest in the growing season characterized by considerable precipitation deficiency. Grzebisz et al [55] and Awgchew et al [56] found that the agronomic efficiency of N fertilization decreases with increasing N rates applied to potatoes. In turn, N-use efficiency expressed by the DMY of celery roots at different rates of N fertilizer ranged from 10.23 to 27.41 kg kg −1 N [57].…”
Section: Effect Of N Fertilization On Agronomic N-indicesmentioning
confidence: 99%